Electrical and mechanical characteristics of (Bi4-xLa x)Ti3O12 ceramics - Pasinee Siriprapa (2018)
Effect of concentration of La doping on phase, microstructure and properties of Bi4-xLaxTi3O12 (where x = 0, 0.25, 0.5, 0.75, 1) ceramics was investigated. X-ray diffraction patterns of the ceramics indicated orthorhombic structure with lattice distortion, especially with higher content of La dopant. All samples showed plate-like morphology with different grain size and orientation. Preferred orientation in undoped and lightly doped BLT ceramics was dominant compared to the samples with high La contents. The reduced preferred orientation in highly doped BLT was accompanied by a decrease in grain size and a slight decrease in density. The temperature dependence of dielectric constant showed a decrease in Tc with increasing La concentration. Dielectric constant measured at room temperature tended to increase with La-content. An addition of La also improved mechanical characteristics of the BIT ceramics. Copyright © Taylor & Francis Group, LLC.